Exponential Stability of Coupled Systems on Networks with Mixed Delays and Reaction-Diffusion Terms - Wenxue Li; Tianrui Chen; Ke Wang (Abstract and Applied Analysis)
This paper is concerned with the stability analysis issue for coupled systems on networks with mixed delays and reaction-diffusion terms (CSNMRs). By employing Lyapunov method and Kirchhoff's Theorem in graph theory, a systematic method is proposed to guarantee exponential stability of CSNMRs. Two different kinds of sufficient criteria are derived in the form of Lyapunov function and coefficients of the system, respectively. Finally, a numerical example is given to show the effectiveness of the proposed criteria.